Perioperative management of patients with genetic multisystem diseases associated with pre excitation - Staikou, Chryssoula; Stamelos, Mattheos; Stavroulakis, Eftyhios (Anestezjologia Intensywna Terapia, 2019)
Pre-excitation is associated with life-threatening arrhythmias. Apart from the well-known Wolff-Parkinson-White syndrome, a number of rare diseases are associated with pre-excitation due to the existence of accessory pathways. The present review aims to focus on anaesthesia and perioperative care of patients with rare genetic diseases associated with pre-excitation due to the existence of a bundle of Kent or other accessory pathways. The Danon disease, Fabry disease and Pompe disease, tuberous sclerosis, Leber hereditary optic neuropathy (LHON), and mitochondrial encephalopathy, lactic acidosis and stroke-like episodes (MELAS) syndrome are genetic multisystem disorders which may involve pre-excitation, usually combined with cardiomyopathy. The anaesthetic management of the above syndromes may become quite challenging. We conducted a PubMed and manual literature search for all types of relevant publications; we identified 58 articles suitable to be included in the present review. According to the literature, a high index of suspicion for the possibility of pre-excitation is required, and anaesthetic drugs and adjuvants should be chosen carefully, in order to prevent or at least not facilitate arrhythmias associated with accessory pathways. The perioperative management should be further tailored to the specific abnormalities of each condition. Multidisciplinary consultation and care, according to the affected organs, are mandatory for a safe outcome. The anaesthetic plan should be focused on preoperative clinical optimization and on case-specific management, tailored to the various systems involved.